DESIGNING AND IMPLEMENTING ASYNCHRONOUS SPEAKING ASSESSMENT: ENGLISH TEACHERS’ CHALLENGES AND OPPORTUNITIES - Dwi Rohmaniatu Silky; Fauzi Miftakh; Mobit Mobit (IKIP Siliwangi, 2023)
Asynchronous learning started to be frequently used to carry out school teaching and learning activities since COVID-19, including for the speaking classroom. This issue changed the speaking assessment used into the asynchronous type to fit the learning method. This study aims to investigate English teachers’ challenges and opportunities in designing and implementing asynchronous speaking assessment. This research use narrative inquiry with semi-tructured interviews as the data collection technique and voice recorder as the documentation. The participant for this research was two English teachers at one of the Vocational High School in Jakarta. The findings showed three challenges and two opportunities while designing and implementing the asynchronous speaking assessment. The challenges were idea and inspiration, authentication of students’ submissions, and more time needed. As for the opportunities, the implementation was flexible, and the need to be more IT-minded. In conclusion, there were both challenges and opportunities while English teachers were designing and implementing the asynchronous speaking assessment. Keywords: Asynchronous Learning; Speaking Assessment; Teachers’ Experience